2021
DOI: 10.1038/s41398-021-01536-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation and gene expression analyses in monozygotic twins identify potential biomarkers of depression

Abstract: Depression is currently the leading cause of disability around the world. We conducted an epigenome-wide association study (EWAS) in a sample of 58 depression score-discordant monozygotic twin pairs, aiming to detect specific epigenetic variants potentially related to depression and further integrate with gene expression profile data. Association between the methylation level of each CpG site and depression score was tested by applying a linear mixed effect model. Weighted gene co-expression network analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The common transcription factors were GATA2, FLI1, CREB1, JUND, E2F1, ESR1, TRAP4, SP1, and GABPA. It has been reported that GATA2, CREB1, and E2F1 were crucial in the maintenance of MDD (41)(42)(43). And ESR1, an estrogen receptor, was also found to be important in depression (44).…”
Section: Discussionmentioning
confidence: 96%
“…The common transcription factors were GATA2, FLI1, CREB1, JUND, E2F1, ESR1, TRAP4, SP1, and GABPA. It has been reported that GATA2, CREB1, and E2F1 were crucial in the maintenance of MDD (41)(42)(43). And ESR1, an estrogen receptor, was also found to be important in depression (44).…”
Section: Discussionmentioning
confidence: 96%
“…The aberrant expression of GRIK2 has been reported to be involved in regions, functional genes, biological function, and pathways that mediate depression disorder. GRIK2 also showed abnormal methylation pattern specific to astrocytic dysfunction associated with depressive psychopathology ( Nagy et al, 2015 ; Wang W. et al, 2021 ). It is interesting to explore the potential association of AS with the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent large-scale genome-wide association studies have failed to replicate some of the BDNF genetic associations from earlier candidate gene studies (Border et al, 2019; Johnson et al, 2017). Although EWASs are several years behind, emerging evidence indicates similar replication issues for candidate DNAm studies in brain-related phenotypes (Shields et al, 2021; Sumner et al, 2022; Wang et al, 2021). Consistent with the recent recommendations of the National Institute of Mental Health Council Workgroup on Genomics (Hyman and Krystal, 2018), we recommend that candidate DNAm studies should be abandoned for EWAS approaches in most cases.…”
Section: Discussionmentioning
confidence: 99%